Changing Dimensions of Malaysian Trade: Beyond Laissez Faire and Dirigiste Approaches - Rajah, Rasiah; H. Osman, Rani; Rokiah, Alavi (Universiti Malaysia Sarawak (UNIMAS), 2000)
The debate on the role of trade in the process of industrial development in developing countries has a long history. For many years developing economies were faced with the grim prospect of facing continued economic stagnation as characterized by Africa and Latin America. It gave rise to a plethora of inward-oriented prescriptions from trade pessimists who have often argued that the capacity of developing economies to grow through export-orientation is limited because of the slow growth in world demand for their exports and the tendency of the terms of trade to disfavour them (Nurkse, 1959; Prebisch, 1959, 1983; Singer, 1950; Stewart, 1976; Lewis, 1980). Such a view was echoed by the Secretary General of the United Nations Committee for Trade and Development (UNCTAD) who maintained the developing countries did not share in three decades of post-war prosperity because of the “existence of basic weaknesses in the mechanisms that link the economies of the two groups of countries” (UNCTAD, 1977: 8-9)